Heat-shock and titanium dioxide nanoparticles decrease SOD and glutathione enzymes activities in Saccharomyces cerevisiae - Capela-Pires, J (2014)
It is well-known that the majority of living organisms depend on oxygen for survival. However, organisms also had to evolve a multitude of enzyme antioxidant defences as superoxide dismutase (SOD1, SOD2), glucose-6-phosphate dehydrogenase (G6PD), glutathione reductase (GR), glutathione peroxidase (GPx), and catalases (CTT1, CTA1) as well as non-enzyme defences as glutathione, to protect their cells from toxicity of reactive oxygen species (ROS). Exposure of living organisms to xenobiotic can also induce significant generation of ROS. Failure of cell antioxidant defences to prevent ROS accumulation inevitably results in oxidative stress. This potentially causes severe oxidative damages in vital biomolecules, thus compromising cell viability. Yeasts can provide a significant contribution to our understanding of oxidative stress, and its consequences on cell death, because its cellular structure and functional organization share many similarities with plant and animal cells. Although ROS accumulation in yeast generally results from cell respiration, environmental stress stimuli can be also another important source. Despite the intensive use of engineered nanoparticles (NPs) in various consumer and industrial products, data on their potential hazards are still rare and mechanisms of action only partially understood. In addition, NPs as titanium dioxide nanoparticles (TiO2-NP) possessing unique physicochemical characteristics such as high specific surface area, high reactivity, and rapid diffusion, which differ from bulk materials of the same composition (TiO2). On the other hand, yeast response to ROS (H2O2) or the toxicity of NPs depends on environmental conditions as temperature. Consequently, the aim of this work was to evaluate the antioxidant response of Saccharomyces cerevisiae, grown in presence of glycerol or glycerol and glucose, to 5 μg/mL TiO2-NP in heat-shock conditions.